Green and Red Luminescent Curcuma and Lawsone Herbal Amalgam as Yellow Emission Source. Issue 14 (12th April 2023) - Sahu, Bhumika; Ghosh, Tanushree; Kandpal, Suchita; Bansal, Love; Rani, Chanchal; Jha, Hem Chandra; Kumar, Rajesh
Abstract: "Herbal electronics" is a very new term tossed for the area where optical and electrical properties of herbal materials are being studied for possible application in electronics. The optical properties of extract solutions obtained from two raw materials namely turmeric, and henna has been studied here using absorption and luminescence spectroscopies. The as‐prepared solutions appear luminescent under UV light and generate two complementary colors, red and green which when mixed together exhibits yellow emission. A careful analysis has been carried out to understand how the two solutions can be mixed to obtain a yellow emission by using a simple Blue/UV LED as excitation source. Obtained emission colors has been qualified using CIE color chart and PL quantum yield have also been calculated. The yellow emission has been demonstrated using a simple set up where a blue led (400 nm) is used as excitation and the mixture solution is used as active luminescent material which emits yellow light with a quantum yield of ∼5 %. Abstract : Optical properties of two herbal products, Henna leaves and Turmeric root reveals that it can be used as raw materials to obtain a yellow emission when mixed in appropriate proportion.